A VISION FOR HUMAN‐MODEL INTERACTION IN INTERACTIVE MODEL‐CENTRIC SYSTEMS ENGINEERING. Issue 3 (6th October 2017) - Rhodes, Donna H.; Ross, Adam M.
ABSTRACT: The Interactive Model‐Centric Systems Engineering (IMCSE) research program arises from the unique opportunity to investigate the various aspects of humans interacting with models and model‐generated data, in the context of systems engineering practice. This paper explores the dimensions of this interaction and shares findings from a recent workshop organized to seed the initial research agenda. Many open areas of inquiry exist; examples include: use cases for stakeholders interacting with models; how multiple stakeholders interact with each other using models and model generated information; facets of human interaction with visualizations and large data sets; and underlying fundamentals such as model purpose and model handling. Realizing the envisioned future for an interactive model‐centric systems engineering experience will require new knowledge and ways of working, and innovation in constructs and technologies. A shared research agenda is proposed as a means to provide a common frame for alignment and synergies of research across the community. Research needs and progress are discussed and several ongoing research projects are briefly discussed.